PEMANFAATAN MEDIA PEMBELAJARAN MOVIE LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN MOTIVASI BELAJAR SEJARAH SISWA KELAS XI IPS 1 DI SMA NEGERI 1 TELUK KUANTAN - Gani, Abdul; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to increase the activity and motivation to learn the history of students of class XI IPS 1 at SMA Negeri 1 Teluk Kuantan in the 2018/2019 school year by utilizing the Movie Learning learning media. This type of research is classroom action research using 2 cycles. Each cycle consists of two meetings covering four stages of implementation, namely: planning, implementation, observation and reflection. Data collection techniques using observation. Data analysis is explained descriptively. The results showed that the percentage of student learning activities in the first cycle was 52.76% with the moderate category increasing in the 79.58% cycle with the high category. Student learning motivation can be seen from the results of increased observation of the questionnaire, the percentage of students' learning motivation in the first cycle was 70.39% an increase in the second cycle to 88.85%. Based on the research results obtained, the use of Movie Learning media can increase student learning activities and motivation.Key Words : Movie Learning